Revealing the importance of interfaces for pure spin current transport - Pfeiffer, A.; Reeve, R. M.; Elphick, K.; Hirohata, Atsufumi; Klaeui, M. (Physical Review Research, 2021)
Spin transport phenomena underpin an extensive range of spintronic effects. In particular spin transport across interfaces occurs in most device concepts, but is so far poorly understood. As interface properties strongly impact spin transport, one needs to characterize and correlate them to the fabrication method. Here we investigate pure spin current transport across interfaces and connect this with imaging of the interfaces. We study the detection of pure spin currents via the inverse spin Hall effect in Pt and the related spin current absorption by Pt in Py-Cu-Pt lateral spin valves. Depending on the fabrication process, we either find a large (inverse) spin Hall effect signal and low spin absorption by Pt or vice versa and a similar effect is seen also for spin current absorption in CoFe-Cu-based devices. We explain these counterintuitive results by the fabrication-induced varying quality of the interfaces, which is directly revealed via a special scanning electron microscopy technique for interface imaging and correlated to the spin transport.
CRIS-Team Scopus Importer:2023-03-27